Die Ordnung des Selbst: Subjektivierung im Kontext von Krise und psychosozialer Beratung - Bohn, Simon (transcript, 2017)
How do individuals present themselves as subjects in the face of individual failure? And how are crises in professional settings of psychosocial counselling systematically accessed and overcome? Bridging the gap between empirical social research and sociological theorising, Simon Bohn shows how participants change their lifestyle and normative frames of self-reference via the (re-)ordering of the self. Using clear and accessible data, the study provides insights into the progression of crises that young adults experience and develops a perspective on subjectivisation that can also be applied to other institutions and social contexts.